Light-scattering Technologies for Field Carcinogenesis Detection: A Modality for Endoscopic Pre-screening - Backman, Vadim (2010)
Colonoscopy has revolutionized colorectal cancer (CRC) screening resulting in a decrease in both CRC mortality and incidence. Despite this, CRC still ranks as the second leading cause of cancer deaths among Americans underscoring the need to both increase availability and accuracy of colonoscopy. The latter considerations provide the impetus for much of the current research into adjunctive imaging technologies. Recent advances in improving detection of dysplasia that have translated into clinical practice include high-definition scopes, narrow-band imaging, and chromo-endoscopy. Another major direction of research into improving endoscopy is determining histology of lesions in situ (“optical biopsy”) with confocal endomicroscopy, fluorescence and elastic scattering spectroscopy. All these techniques are of great promise in improving delivery of endoscopy but, to date, have not addressed the potentially more important hurdle associated with logistic challenges of providing accurate CRC screening for the entire at-risk population.